1986
DOI: 10.1095/biolreprod35.4.987
|View full text |Cite
|
Sign up to set email alerts
|

Uterine growth-promoting effects of relaxin: a morphometric and histological analysis

Abstract: The hormone relaxin has been implicated in the regulation of several processes in the reproductive tract during pregnancy and parturition. This study investigated the uterine effects of relaxin in immature and mature ovariectomized, estrogen-primed rats using morphometric and histochemical analysis. Rats were sprayed at 30 or 70 days of age and given estrogen (5 micrograms) 7 days later. After a week, they received an injection of porcine relaxin (100 micrograms) and were killed 6 h later; controls received ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0
2

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(27 citation statements)
references
References 0 publications
3
22
0
2
Order By: Relevance
“…Abbreviations used in this paper: [Ca2"]i, intracellular Ca2" concentration; D-Arg, D-arginine; D-NAME, Nw-D-arginine methylester; L-Arg, L-arginine; L-NAME, Nw-L-arginine methylester; MC, mast cell; MeArg, Nw monomethyl-L-arginine; Quin-2 AM, Quin-2 acetoxymethylester; RLX, relaxin. our laboratory on the mammary gland, mesenteric vessels, and pigeon crop sac (4)(5)(6), as well as studies of other authors on the rat uterus (7), RLX was shown to cause striking enlargement of microvessels. Interestingly, our findings on the mammary gland of mice given RLX systemically (8) revealed that vasodilation was not accompanied by a concurrent release of granules from mast cells (MCs), thus suggesting that the action of RLX is independent of the release of vasoactive mediators contained in the MC granules, such as histamine.…”
Section: Introductionmentioning
confidence: 58%
“…Abbreviations used in this paper: [Ca2"]i, intracellular Ca2" concentration; D-Arg, D-arginine; D-NAME, Nw-D-arginine methylester; L-Arg, L-arginine; L-NAME, Nw-L-arginine methylester; MC, mast cell; MeArg, Nw monomethyl-L-arginine; Quin-2 AM, Quin-2 acetoxymethylester; RLX, relaxin. our laboratory on the mammary gland, mesenteric vessels, and pigeon crop sac (4)(5)(6), as well as studies of other authors on the rat uterus (7), RLX was shown to cause striking enlargement of microvessels. Interestingly, our findings on the mammary gland of mice given RLX systemically (8) revealed that vasodilation was not accompanied by a concurrent release of granules from mast cells (MCs), thus suggesting that the action of RLX is independent of the release of vasoactive mediators contained in the MC granules, such as histamine.…”
Section: Introductionmentioning
confidence: 58%
“…In previous studies, RLX has been shown to have powerful vasodilatory action in both sexes (Bigazzi et al 1986, Vasilenko et al 1986, Masini et al 1997, Danielson et al 1999. Therefore, in the current study, we used male rats to exclude any possible influence of endogenous RLX and ovarian steroids on the experimental results, as may have occurred if using cycling female rats.…”
Section: Methodsmentioning
confidence: 99%
“…These cells are sensitive to substances known to decrease or increase sinusoidal blood flow, such as ethanol (Hijioka et al 1991) and bile acids (Pak & Lee 1993) respectively, as well as to the vasorelaxant hormone relaxin (RLX). RLX is a peptide hormone typical of pregnancy (reviewed by Bani 1997) which has been shown to cause striking vasodilation in several organs (Vasilenko et al 1986, Masini et al 1997, Danielson et al 1999. Among these organs, there are the mesenteric microvessels (Bigazzi et al 1986), which are thought to play an important role in the regulation of portal blood flow and hence, indirectly, in liver perfusion (Rappaport 1973).…”
Section: Introductionmentioning
confidence: 99%
“…Vasodilation in arterioles, capillaries, and venules is a common response to relaxin in reproductive tissues (Vasilenko et al, 1986;Bani et al, 1988;Lee et al, 1992), heart (Bani-Sacchi et al, 1995;Masini et al, 1997;Bani et al, 1998b), liver (Bani et al, 2001), and cecum (Bigazzi et al, 1986). Relaxin is a potent vasodilator in arteries (Conrad, 2010;McGuane et al, 2011b), although the effect is vessel specific (McGuane et al, 2011b).…”
Section: Physiologic Roles Of Relaxin Family Peptide Receptors Andmentioning
confidence: 99%